Da dignidade da política: invenção da África do Sul Democrática (décadas 1980-1990) - Silva, Cristiane Mare da (2021)
In this text, I share reflections on how Madiba and his companions faced the ingenious forms of political domination of modernity in South Africa, between 1985 and 1999, their combination of terror, bureaucracy, racism, neoliberal universe, from the perspective of a democratic action denying the use of violence against its adversaries, having persuasion as a crucial point in the intense work of overcoming the apartheid policy as a political racial regime. Through the analysis and interpretation of his prison letters, new biographies, sources from the South African press and documents available online, we realized that Mandela, the ANC, UDF, COSATU, among other social groups, were reinventing a political practice and thinking that made possible the emergence of South Africa as a political community with a comprehensive profile. Represented in the country's positive image at the 2010 FIFA World Cup, and in the admired figure of Nelson Mandela, Nobel Peace Prize Laureate. To historicize this process, from promises and dilemmas to achievements, encompasses what we intend to address in this work. Inspired by the readings of Frantz Fanon, Hannah Arendt, Michel Foucault and Achille Mbembe, we understand that the dilemmas of that southern African country lie at the center of the civilization crisis in which we live, since the last quarter of the 20th century, marked by the advent of globalization, neoliberalism and hedonistic individualism